The Role of State on Social Justice: An Analysis from Ibn Sina’s Perpective - Ismail, Nurizal; Cahyo, Eko Nur (AL-IKTISAB: Journal of Islamic Economic Law, 2018)
Every nation attempts to provide welfare for its citizen such as better economic growth, social security and better life. All economic systems either Capitalism or Socialism has the same objective to provide welfare for its nation. In Islam, welfare lies in complete justice, mercy, welfare, and wisdom; anything that departs from justice to injustice, from mercy to harshness, from welfare to misery and from wisdom to folly has nothing to do with the Shari’ah. The Islamic concept and values on welfare of the society are related to Islamic economic history that can be found from Qur’an and Sunnah and Islamic literatures such as history, fiqh, philosophy, kalam, and tasawwuf. it is assumed that there are some Muslim scholars whose works are related to role of state on welfare. Therefore, the study attempts to know the role of state on social justice derived from Ibn Sina and give some critical study on his thought. To achieve its objectives; this study employs qualitative research that refers to the meanings, concepts, definitions, characteristics, metaphors, symbols and descriptions of the matter understudy. Moreover, it is used content and descriptive analysis to get finding of the study. The data collection is generated from Islamic sources. The finding of this study is that Ibn Sina’s thought on state role to promote social justice containts of providing law, job opportunities and social security. These roles of state can contribute to harmony, peace and welfare of the society.